Exchanging ginger for chilli?: The social ecology of a world bank-funded higher education project in Sri Lanka - Wijetunga, LM (2021)
Internationally funded education projects in the majority world are a rich field of study, which intersects multiple disciplines from education to economics to postcolonial studies. As a former colony, currently a low-middle income country, Sri Lanka has been at the receiving end of these funds – grants and loans – for years. While there is much criticism against such international funders imposing a new imperialism on the majority world, there is also literature that represents the international funders as helpful actors. In this dichotomy what is less present are the voices of those from the majority world countries and their narratives. This study explores the social ecology of academics working on a World Bank-funded project in the higher education field in Sri Lanka. Adopting a Constructivist Grounded Theory approach, it uses interviews to uncover theories emerging from the data. The emerging theories are two: one explores the concept of trust and notes that the lack of trust in one’s government, State, and State systems catalyse the academics to be open to help from international organisations like the World Bank; the second is based on the concept of obligation and identifies that associative political obligation to the education system drives the individuals, thus prioritising short-term practicalities over long-term ideologies. These two theories help both explain the social ecology of academics, as well as complicate the existing understanding of the internationally funded projects in the majority world. In situating these two emergent theories in the larger literature, this study suggests that the World Bank should be represented more dynamically; to truly capture the nature of the World Bank, this study suggests it be approached as an epistemic actor and/or a theorist, who permeates multiple facets of social ecology.